Climbing Perch (Anabas testusdineus) Culture With Aquasimber System Fed With The Addition Of Bromelain Enzyme - Safitri, Nadia; Putra, Iskandar; Pamukas, Niken Ayu (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
This study aims to determine the best dose of bromelain enzyme to increasing the growth rate and survival rate of climbing perch reared with aquasimber system. The research was conducted on January 1 to February 10, 2022 at the Aquaculture Hatchery, Faculty of Fisheries and Marine Affairs, Riau University. The research method is a Completely Randomized Design (CRD) with one factor, five treatments and three repetitions. And the use of a 100 L volume bucket container. The treatment levels applied in this study were P0 (control), P1 5 g/kg feed, P2 10 g/kg feed, P3 15 g/kg feed, P4 20 g/kg feed. The results showed that the difference in bromelain enzyme doses had a significant effect (P<0.05) on the growth and survival of climbing perch. The best treatment was obtained at P3 15 g/kg with temperature (28.2-29.30C), pH 6.4-7.3, DO (6.6-7.9 mg/L) , and level of NH3 (0.0010-0.0045 mg/L), absolute weight growth (3.98 g), absolute length growth (3.53 cm), specific growth rate (1.80%), feed efficiency (41.12%) , feed conversion(2.43%), survival (100%), content ofenzyme bromelain (0.19 IU/mL)